Cokie : a life well lived - Roberts, Steven V., 1943- (HarperCollins Publishers, 2021)
Cokie Roberts' husband Steve Roberts reflects not only on her many accomplishments, but on how she lived each day with a devotion to helping others. For Steve, Cokie's private life was as significant and inspirational as her public one. Her commitment to celebrating and supporting other women was evident in everything she did, and her generosity and passion drove her personal and professional endeavors.